THE AUTHORITY OF NOTARIES IN FILLING LEGAL GAPS IN ISSUING INHERITANCE CERTIFICATES FOR FOREIGN CITIZENS FOLLOWING THE ENACTMENT OF LAW NUMBER 6 OF 2023 CONCERNING THE STIPULATION OF GOVERNMENT REGULATION IN LIEU OF LAW NUMBER 2 OF 2022 ON JOB CREATION - Rahmawati, Ayu; Kusumadara, Afifah; Masykur, M. Hamidi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The purpose of this research is to provide an overview of the legal vacuum (rechtsvacuum) in the proof of heirs as legitimate heirs of a deceased foreign national. This research is normative juridical research. It uses a normative juridical approach with two methods: statutory and conceptual. The sources of legal materials consist of primary sources (legislation), secondary sources (academic manuscripts, legal journals, books, articles), and tertiary sources (legal dictionaries, KBBI). The literature study method is used to search for legal sources. The analysis of legal materials is conducted using teleological interpretation and the specialization construction technique (rechtsvervijnings). The research results show that granting Property Rights (Hak Milik) for apartment units (Sarusun) to Foreign Citizens (WNA) in Indonesia is not new and has long been practiced as an effort to attract investment and provide facilities for foreign nationals who contribute to national development. However, there is a legal vacuum regarding the creation of Inheritance Certificates (Surat Keterangan Waris - SKW) for foreign heirs, which is important for proving their status as legitimate heirs and conducting legal transactions related to the inheritance. To address this legal vacuum, it is recommended that the creation of SKW for heirs of foreign nationals should be carried out before a Notary. The main reason for choosing a Notary is because they have the authority to create authentic deeds, have a wide reach throughout Indonesia, and are not limited by religious factors in creating SKW. Additionally, deeds made by a Notary have stronger legal force compared to SKW in letter form. Therefore, this arrangement is expected to provide legal certainty for foreign nationals owning Sarusun in Indonesia and their heirs.